if alpha and beta are zeros of p(x)=2x2-x-6,then find the value of alpha^-1+beta^-1
Answers
Answered by
73
P(x)= 2x^2 -x -6
So by multiply the 1st and 3rd term it guves - 12 which suggests that one root is - ve.
P(x) = (2x^2 - 4x) (3x - 6)
= 2x (x - 2) +3 (x - 2)
= (2x + 3) (x - 2)
Alpha= 2 and Beta= - 3/2
Alpha^-1 + Beta^-1 = 1/2 - 2/3
= - 1/6
So by multiply the 1st and 3rd term it guves - 12 which suggests that one root is - ve.
P(x) = (2x^2 - 4x) (3x - 6)
= 2x (x - 2) +3 (x - 2)
= (2x + 3) (x - 2)
Alpha= 2 and Beta= - 3/2
Alpha^-1 + Beta^-1 = 1/2 - 2/3
= - 1/6
Rachel3442:
Ty
Answered by
1
Answer:
Plz see the attachment
HOPE IT'S HELPFUL FOR YOU
Attachments:
![](https://hi-static.z-dn.net/files/d16/04a104b22abce618b325b08d31fdf271.jpg)
Similar questions